REGULATION OF OPEN BANKING IN NIGERIA: BALANCING INNOVATION AND PRIVACY - Ohiro, Oghomwen Rita; Odudu, Keseme Phillip (ABUAD Private and Business Law Journal, 2019)
Open banking has become a game-changing strategy in the financial sector, aimed at improving innovation, competition, and overall customer experience. This study explores the possibility of introducing technological advancements in banking through open banking systems while ensuring privacy protection. It examines the legal aspects of regulating open banking in Nigeria and emphasizes the importance of achieving a balanced approach that encourages innovation while maintaining rigorous regulatory standards. This paper employs a doctrinal research methodology, combining legal analysis and comparative studies to assess Nigeria’s current regulatory landscape and identify any gaps. Drawing on the United Kingdom’s regulatory model as a benchmark, the paper evaluates the effectiveness of Nigeria’s regulations governing open banking. The findings emphasize the necessity of enhancing the regulatory framework to address the unique challenges posed by open banking in Nigeria. By providing insights and recommendations, this paper seeks to guide policymakers in striking a harmonious balance between innovation and privacy within the Nigerian open banking ecosystem.